Freeze concentrated apple juice maintains its flavor - Yoda, Tsuyoshi (Sci Rep, 2021)
Concentrated juices are sources of alcoholic drinks. Juice concentration may be achieved using different methods, such as freezing or heating. High temperatures in the process of juice concentration damage heat-sensitive components, such as aromatic compounds. Although the freezing process of juice concentration has been studied, analyses have been inadequate, particularly in addressing flavors. Therefore, we investigated the characteristics of freezing and heating during apple juice concentration in the context of flavor. We found that a total of 97 compounds were found in fresh juice, and freeze-concentrated juice retained 57 of these compounds. Interestingly, freezing led to the generation of 37 flavor compounds. Furthermore, people had difficultly differentiating between intact and frozen concentrated juice. The ratios were almost same between those who correctly identified (28%) and those who incorrectly identified fresh and reconstituted freeze-concentrated juice (25%). We discuss the mechanisms of flavor generation on freezing concentration with regard to the increases in enzymatic activity or other causes. Our study showed that the methods of juice concentration that utilize freezing retain flavor better. These data will benefit juice concentration processes of apples and other fruits in the future.